135k views
5 votes
Identify the number of solutions of the system of linear equations. 5x+y−z=6 x+y+z=2 12x+4y=10

User Svz
by
5.3k points

1 Answer

2 votes

Answer:

x =
(19)/(12) y =
(-(9)/(4) ) z =
(8)/(3) One solution for each variable.

Explanation:

5x + y − z = 6

x + y + z = 2

12x + 4y = 10

The first thing we need to do is solve for x in the 3rd equation because it inly have 2 variables, x and y.

12x + 4y = 10 Subtract 4y from each side

12x + 4y - 4y = 10 - 4y

12x = 10 - 4y Pull 2 out on the right side

12x = 2(5 - 2y) Divide each side by 12

12x/12 = 2(5 - 2y)/12

x = 2(5 - 2y)/12

x = (5 - 2y)/6

Now we plug in our x value into the 2nd equation and solve for z

x + y + z = 2


(5-2y)/(6) + y + z = 2 Multiply each side by 6

6(
(5-2y)/(6) + y + z) = 2 * 6

6(
(5-2y)/(6) + y + z) = 12

5 - 2y + 6y + 6z = 12 Combine like terms

5 + 4y + 6z = 12 Subtract 5 from each side

5 - 5 + 4y + 6z = 12 - 5

4y + 6z = 7 Subtract 4y from each side

4y - 4y + 6z = 7 - 4y

6z = 7 - 4y Divide each side by 6

6z/6 = (7 - 4y)/6

z = (7 - 4y)/6

Now we solved for z and x, so in the 1st equation we plug in x and z.

5x + y − z = 6

5(
(5-2y)/(6)) + y -
(7-4y)/(6) = 6 Multiply each side by 6

6*(5(
(5-2y)/(6)) ) + 6y - 6(
(7-4y)/(6)) = 6*6

6*(5(
(5-2y)/(6)) ) + 6y - 6(
(7-4y)/(6)) = 36

5(5 - 2y) + 6y - 7 - 4y = 36

25 - 10y + 6y - 7 - 4y = 36 Rearrange to make it easier to combine terms.

25 - 7 - 10y + 6y - 4y = 36

18 - 8y = 36 Subtract 18 from each side.

18 - 18 - 8y = 36 - 18

- 8y = 36 - 18

- 8y = 18 Divide each side by -8

- 8y/-8 = 18/- 8

y = 18/- 8

y = - 9/4

Now we plug our answer for y back into the 3rd equation and solve for the value of x.

12x + 4y = 10

12x + 4
(-(9)/(4) ) = 10

12x - 9 = 10 Add 9 to each side

12x - 9 + 9 = 10 + 9

12x = 10 + 9

12x = 19 Divide each side by 12

12x/12 = 19/12

x = 19/12

Now we have a value for x and y so plug these into the 2nd equation to sovle for z.

x + y + z = 2


(19)/(12) +
(-(9)/(4) ) + z = 2 We need to find the common denominator in order to add.


(-(9)/(4) ) *
(3)/(3) =
-(27)/(12)


(19)/(12)
-(27)/(12) + z = 2


-(8)/(12) + z = 2 Add
-(8)/(12) to each side


-(8)/(12)
+ (8)/(12) + z = 2
+ (8)/(12)

z = 2
+ (8)/(12) Reduce
+ (8)/(12) to
(2)/(3)

z = 2 +
(2)/(3) To add find a common denominator.


2 * (3)/(3) = (6)/(3)

z =
(6)/(3) +
(2)/(3)

z =
(8)/(3)

So there is 1 solution for each variable.

User Sandeep Sharma
by
6.6k points